The correlation between biotribological function and structural characteristics of bamboo rat teeth. Issue 4 (15th November 2022) - Ning, Zhenwu; Zhou, Zhongrong; Zheng, Jing
Abstract: Chinese bamboo rats consume a diet that consists mainly mechanically demanding bamboo. The ability of the rats to process food depends on the capacity of their teeth to resist wear during biting and chewing. The mechanisms of the bamboo rat teeth were determined by investigating and correlating the structure and tribological properties of the teeth. The rat's incisor has a cutting‐edge cusp and outer enamel iron pigmentation, making the teeth harder, more resistant to acid attacks, and improving the resistance to cracking. Additionally, the incisor is designed to self‐sharpen. The complex morphology at the macroscale, and the three‐dimensional fabric body formed by densely packed rods and inter‐rods at the microscale of molar enamel benefit molar rapid capture and effective breaking of bamboo, resisting the high stresses required to process bamboo without wear. The results of the structure–function relations of bamboo rat teeth in this study may provide new ideas for improving plant cutting and grinding tools.